CONSTRUÇÃO DO CONCEITO DE FUNÇÃO: UMA EXPERIÊNCIA DE ENSINO-APRENDIZAGEM ATRAVÉS DA RESOLUÇÃO DE PROBLEMAS - Zatti, Sandra Beatris (2010)
In this paper, we present the results of a qualitative research, related to the teaching and learning of mathematics. Therefore, it is the product of an investigation on the contributions that problem solving, as a teaching methodology, can bring to the teaching and learning of the concept of function to high school students. The research was conducted with a group of high school first grade, composed of 19 students of the Escola Estadual Professora Maria Rocha, located in Santa Maria-RS. The instruments used in data collection were: questionnaire to the class - in order to verify the expectation of students regarding the use of a new teaching methodology - participant observation in the classroom and the teacher-researcher s field diary. The development of activities in the classroom took place by applying a sequence of mathematic problems, and the teacher-researcher used problem solving as teaching strategy, suiting the steps suggested by Onuchic (1999): 1) Form groups and deliver the activity, 2) The teacher's role; 3) Results on the board, 4) Plenary and analysis of results, 5) Consensus and formalization of concepts. The analysis of data obtained during the field work points out to the importance of working on mathematics in a way more connected to students' everyday lives. We may infer also that problem solving is an effective strategy in teaching and learning of mathematics, both as a teaching method to be used by teachers in classroom and to create a new attitude in students: motivation to solve other problems and pleasure with mathematics that is learned in school.